4(x-3)+5=53

Simple and best practice solution for 4(x-3)+5=53 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x-3)+5=53 equation:


Simplifying
4(x + -3) + 5 = 53

Reorder the terms:
4(-3 + x) + 5 = 53
(-3 * 4 + x * 4) + 5 = 53
(-12 + 4x) + 5 = 53

Reorder the terms:
-12 + 5 + 4x = 53

Combine like terms: -12 + 5 = -7
-7 + 4x = 53

Solving
-7 + 4x = 53

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '7' to each side of the equation.
-7 + 7 + 4x = 53 + 7

Combine like terms: -7 + 7 = 0
0 + 4x = 53 + 7
4x = 53 + 7

Combine like terms: 53 + 7 = 60
4x = 60

Divide each side by '4'.
x = 15

Simplifying
x = 15

See similar equations:

| 4(2w-3)=2(3w+5) | | t^3+6t^2=25t+150 | | 3(X-2)=Xm+7 | | 5x+6=2x-2 | | 14=-5y+3(y-2) | | 18y=-20+19y | | -17-4k=3k+13-5k | | 0=-7r-3r | | 3(2x+5)=-37+22 | | 29=8+3x | | 25(x^2)-20x+4=0 | | 3g+9=4g | | 10-7k=-(8k-7) | | 8-9z=-5z | | 5-3(X-4)=11 | | -8=6(v-4)-8v | | -34+4p=-7(8+p) | | 7x-44=10-5x | | 0=7+5x^2-2x^3 | | 5+6h=-5+5h | | 4/5t+1=t+1/2 | | -3j-4j-1=-3j+7 | | 34=-8y+6(y+8) | | 16=p-5p | | -10-2n=-n | | 8n=7n-3 | | y=x^6-7x | | 9d=9+10d | | 4x^2-35x-414= | | 3w+15=48 | | 10B+8=68 | | -5(r+4)=-72 |

Equations solver categories